Pandangan IPQOH Kota Medan terhadap Seni Membaca Al-Qur’an dengan Langgam Jawa (Analisis Nilai Estetis Al-Qur’an) - Hanif, Farhan (TSAQOFAH, 2023)
On May 15, 2015 the government of the Republic of Indonesia held an Isra' Mi'raj event at the State Palace in Jakarta. Muhammad Yaser Arafat, one of the Qori chosen to recite the Qur'an at the event. However, he read the Koran in Javanese style, this event has reaped pros and cons for some people, both nagham experts and scholars. As for the method that the author uses in this research, namely the descriptive qualitative method, namely the research method by discussing the problems to be studied, namely interviewers and resource persons. The results of the interview are quoting the opinion of Ustadz Muhammad Zaini Lubis. He is of the opinion that the use of rhythm in reading the holy verses of the Qur'an other than the Arabic rhythm or style is not justified, whether reading the whole verse or only inserting a part of the style other than the Arabic style in the middle. But in the context of its aesthetic value, because the purpose of art is to be enjoyed by listeners, as long as the rhythm reaches the listener's heart and is enjoyed by the listener, it is permissible to use variations of the Javanese style by following a predetermined tajwid order.